y-1/3-y-2/4=1 solve please
Answers
Answered by
3
Step-by-step explanation:
Answer
3
y−1
−
4
y−2
=1
12
4y−4−3y+6
=1
⇒y+2=12
⇒y=10.
Answered by
1
Step-by-step explanation:
Given:-
(y-1)/3-(y-2)/4=1
To find :-
Solve the given equation?
Solution:-
Given equation is (y-1)/3-(y-2)/4=1
LCM of 3 and 4 = 12
=> [4(y-1) -3(y-2)]/12 = 1
=> (4y-4-3y+6)/12 = 1
=> (y+2)/12 = 1
=> y+2 = 1×12
=> y+2 = 12
=> y = 12-2
=> y = 10
Therefore, y = 10
Answer:-
The solution for the given equation is 10
Check:-
If y=10 then
LHS = (y-1)/3-(y-2)/4
=> (10-1)/3 - (10-2)/4
=> (9/3) -(8/4)
=> 3-2
=> 1
=> RHS
LHS = RHS is true for y = 10
Similar questions